Leading for Truth and Reconciliation: Parent, Family and Community Empowerment in the Learning of Their Children - Benoit, Shendah M (Scholarship@Western, 2023)
Almost ten years after the release of the Truth and Reconciliation Commission’s Calls to Action, there remains much for schools to improve for First Nation, Metis, and Inuit students and their families. Focusing on Call to Action 10.vi: enabling parents to fully participate in the learning of their children, identifies a problem of practice. The impact of residential schools and systemic racism have created a separation between families and their children’s learning as well as a lack of trust in the school. Using the assumptions of positive organizational scholarship to understand the complex system of my school, as well as the belief that student learning is influenced by family, community and school, this organizational improvement plan uses an appreciative inquiry organizational model to implement change to the partnership between school and home. The proposed solution is an active partnership between teacher and family or community members to deliver some of British Columbia’s curricular competencies, and create opportunities for families to be empowered in their children’s learning. Leading this complex work will require the disposition of a compassionate systems leader balancing personal mastery, relational awareness and systems thinking. For decades research has demonstrated the positive influences of the parent in the learning of the child. Little of this considers the equitable inclusion of First Nation, Metis, and Inuit families.